The Influence of TikTok Beauty Content Consumption on Teenage Girls’ Purchase Intention for Skincare Products - An'Nisa Khoirun Nur Mulyono; David Rizar Nugroho; Enden Darjatul Ulya; Mulyono Mulyono (Jurnal Ilmiah Multimedia dan Komunikasi, 2026)
This study examines the influence of beauty content consumption on TikTok social media on purchase intention for skincare products among teenage girls. The study is motivated by the high usage of TikTok and the impact of beauty content on young consumers' behavior. It aims to analyze the effect of frequency, intensity, and content type on the stages of the AIDA model (attention, interest, desire, action). A quantitative survey method was applied to 108 teenage girls aged 13–18 who are active TikTok users. Data analysis used simple linear regression to test relationships between variables. Results show that beauty content consumption on TikTok positively and significantly affects each AIDA stage, highlighting TikTok’s role as an effective medium to influence teenage girls' purchase intentions. The study concludes that frequency, intensity, and content type are important considerations for effective marketing strategies in the beauty industry.